ANALISIS PRODUKSI LIMBAH TANAMAN PANGAN SEBAGAI PAKAN TERNAK SAPI DI KABUPATEN BOLAANG MONGONDOW UTARA - Pomolango, Ramlan; Kaunang, Ch L; Elly, F H (ZOOTEC, 2016)
PRODUCTION  ANALYSIS  OF FOOD  CROP WASTE PRODUCT AS CATTLE FEED IN NORTH BOLAANGMONGONDOW REGENCY. Cattle can be used as the main economical source giving added value in farm of the farmers to support their family needs in North Bolaang Mongondow regency. Farmers utilized food crop waste product for cattle feed maintenance. The problem was that the food crop waste product potential was unknown to support cattle development in the farm of the farmers. The objective of this study was to analyze food crop waste product potential. Materials in this study were involving food crop area, type of food crop waste product, and cattle. Research method was applied by survey method involving primer and secondary data. Data were analyzed by proximate analysis conducted by Research Institution and Industrial Standardization, Manado and descriptive analysis. Agricultural waste product was local feedstuff as crude fiber source that can be used for cattle feed. The potential feedstuff was calculated on the basis of feedstuff production multiplied by crop cultivation area size and expressed in dry matter (DM). The highest potential of DM was the wet rice paddy straw, followed by dry rice paddy straw, corn straw, sweet potato leaves, cassava leaves, green bean straw, and peanut straw. This study concluded that dry matter productions of wet rice paddy straw, corn straw and peanut straw were highly produced in Sanggkub district. Dry matter productions of dry rice paddy straw, cassava leaves, and sweet potato leaves were highly produced in East Bolaang Itang district, while dry matter production of green bean straw was highly produced in West Bolaang Itang district. Based on this research it can be suggested to introduce the technology related to the preservation of food crop waste product in North Bolaang Mongondow regency.   Keywords: Waste product, food crop, cattle, North Bolaang Mongondow regency.